Probiotic foods in health and disease - Nair, G. Balakrish; Takeda, Yoshifumi, 1935-; National Institute of Cholera & Enteric Diseases (India); Indian Council of Medical Research (Boca Raton, FL : CRC Press ; New York, NY : Science Publishers, 2011)
'Probiotic Foods in Health and Disease' compiled by leading experts is a blend of fundamental and applied research related to the use of these important organisms in enhancement of human health. The book aims at covering all aspects of the intestinal microflora and offers a comprehensive review of the broad array of effects that can be attributed to probiotic usage. While the thrust remains the latest and most exciting findings in the field of gut health, it also opens a window to the possible role of probiotics beyond the gut such as oral health care, allergic disorders and women's health. The book also reviews pertinent legislation regulating the use of probiotics across the globe with special emphasis on Japan, a country which pioneered the establishment of a regulatory framework for functional foods, or foods that promote a health benefit besides providing basic nutrition. Each chapter offers a insight of the topic, reviews current research and discusses future direction. Most of the references that have been cited in the book chapters are recent, exploit modern methodologies, good controls and rational explanations for the probiotic benefits'--Provided by publisher.
(Publisher-supplied data) Probiotic Foods Today and the Future: Where Science and Commerce Need to Meet / Gregor Reid, Jean Maclaim, Ruben Hummelen, Joke Dols and Wayne L. Miller -- Probiotics- Guidelines, Regulations and Health Claims / B. Sesikeran and R. Hemalatha -- Legislation of Probiotic Fermented Milk Drinks,An Important Functional Food in Asia / Akiyoshi Hosono --'FOSHU' Japanese Regulations for Probiotic Foods / Osamu Chonan -- Probiotics: A Pharmacologist's Perspective / S.D. Seth and Mohua Maulik -- Host-microbe Interactions in the Gut: A Microbiologist's Perspective / R. Chaudhry, V.D. Bamola and P. Panigrahi -- Probiotics and Intestinal Defensins: Augmenting the First Line of Defence in Gastrointestinal Immunity / Dipankar Ghosh -- Toward the Identification of Gut Microbial Markers Associated to Irritable Bowel Syndrome / Raish Oozeer and Patrick Veiga -- Probiotics and their Role in Reducing Allergic Disorders / .K. Kabra and Rakesh Lodha -- Oral Microflora, Oral Health and Probiotics / Mahesh Verma and Ruchika Roongta Nawal -- Proiotics and Women's Health / Indrani Ganguli, Mala Srivastava and Mamta Dagar.
Includes bibliographical references and index.
Keywords: Probiotics -- pharmacology; Food, Fortified -- microbiology; Lactobacillus -- metabolism; Nutritive value; Probiotics -- Therapeutic use